The Centre d'Accueil Nord-Africain: social welfare and the 'problem' of Muslim youth in Marseille, 1950–1975. (1st December 2019) - Harris, Dustin Alan
Abstract: In recent years, historians have paid increasing attention to social welfare initiatives undertaken in post-Second World War France to integrate Muslim Algerian migrants into French society and the legacies of these initiatives after decolonization. This article engages with this field of research by focusing on a topic it has largely ignored—the so-called 'problem' of the integration of Muslim youth. The central point of focus is the Centre d'Accueil Nord-Africain (CANA), a private welfare association founded in Marseille in 1950 that well into the mid-1970s considered the integration of male Muslim North African youth its central objective. In exploring the origins and operations of the CANA over a roughly twenty-five-year period, this article offers new insights into issues of continuity and change related to the target, approach and objectives of integrationist social welfare for Muslim North Africans in France before and after decolonization.